Smart interactive whiteboard in EFL class at Islamic university - Pratama, Aryawira; Rozal, Edi; Andriani, Reni; Sumardi, Mayang Sastra; Putri, Rahmadani; Mahmudah, Khotimah; Sakunti, Sri Ramdayeni (Universitas Muhammadiyah Malang, 2024)
This research aims to investigate students’ perception of using Smart Interactive Whiteboard in the English as a foreign language (EFL) classroom in the State Islamic University in Jambi city. This research employs a quantitative survey method, utilizing a questionnaire as the primary data collection tool. The questionnaire consisted of 26 five-point Lickert-scale items in order to measure the students’ perceptions about (1) Perceived Learning Contribution, (2) Motivation, (3) Perceived Efficiency, and (4) Perceived Negative Effects. The results of the survey show that students like having smart, interactive whiteboards in the classroom. The results show that these technological tools help people learn, get motivated, feel like they are working well, and don't have any bad affects. The combination of audio and visual elements makes it easier to understand and provides a stimulating learning environment. Students also say they are more engaged, focused, involved, and excited about learning. Smart, interactive whiteboards are thought to make classrooms more visible, more organized, and better at keeping track of time. The fact that most students disagree with the idea that these tools have bad results shows that they like using them. Overall, the results show how smart interactive whiteboards can be benefited for positive learning experiences, motivation, efficiency, and student engagement in a positive and pleasant learning atmosphere.